Effectiveness of 23-valent pneumococcal polysaccharide vaccine on diabetic elderly. Issue 26 (June 2016) - Kuo, Chia-Sheng; Lu, Chia-Wen; Chang, Yu-Kang; Yang, Kuen-Cheh; Hung, Shou-Hung; Yang, Ming-Ching; Chang, Hao-Hsiang; Huang, Chi-Ting; Hsu, Chih-Cheng; Huang, Kuo-Chin
Abstract : Abstract: Diabetes mellitus is associated with increased risk of pneumonia, and 23-valent pneumococcal polysaccharide vaccine (PPV23) is recommended for prevention of pneumonia. However, the effectiveness of PPV23 remains unclear in the older diabetic patients who usually have compromised immune function. We used data extracted from the Taiwanese National Health Insurance Research Database (NHIRD) from 2000 to 2009 to conduct a population-based retrospective cohort study, comparing the incidence of pneumococcal diseases among PPV23-vaccinated and propensity-score matched PPV23-unvaccinated groups in diabetic elderly. The primary outcome was invasive pneumococcal diseases (IPDs), and the secondary outcomes were medical utilization. PPV23-vaccinated group had reduced risks of IPD (adjusted OR: 0.86, 95% CI: 0.78–0.94), respiratory failure (0.84, 0.77–0.93), and shorter length of hospitalization (−1.27 ± 0.19 days, P value: 0.0012). In flu-vaccinated group, subjects who received PPV23 had reduced risks of IPD, hospitalization, and respiratory failure; had shorter lengths of hospitalization; and less medical costs, than those without receiving PPV23. In not flu-vaccinated group, PPV23 vaccination was associated with reduced risks of IPD and respiratory failure. Receiving both vaccines could bring better protection in IPD, hospitalization, visits of emergency department, and respiratory failure. PPV23 vaccination was effective in prevention of pneumococcal diseases and reduction of medical utilization in diabetic elderly aged 75 and more. Receiving both vaccines resulted in better outcomes than PPV vaccination alone.